Prevalence and factors associated with depression amongst pregnant women at Helene Franz Hospital of the Limpopo Province, South Africa - Ramohlola, Motjatji Cathrine (My University, 2021)
Pregnancy and childbearing are most of the crucial milestones in women’s lives as they look forward to becoming mothers. During this time, they have positive expectations while pregnant, however, the physical, hormonal, neurotransmitters and psychosocial changes that occur can make pregnancy to be stressful and overwhelming. The disability associated with depression and its impact on maternal and child health has important implications for public health policy. While the prevalence of postnatal depression is high, there are no prevalence data and associated risk factors on antenatal depression in Helen Franz Hospital of Limpopo Province, South Africa. The purpose of this study was to determine the prevalence and factors associated with depression amongst pregnant women at Helene Franz Hospital. Methodology: A quantitative retrospective design was used in the study and a sample size of 336 was required which was calculated based on the 95% confidence interval, 5% sampling error and 38.5% prevalence of depression amongst pregnant women in KZN. A self-administered questionnaire with close-ended questions which was adopted from the Edinburgh postnatal depression scale was given to the participants to complete. The scoring of the questionnaire was that the maximum score was 30 and the persons who scored 10 or greater were considered depressed according to the Edinburg scale for assessing depression. Data were analysed using SPSS V.21.0 and a p-value of less than 0.05 was considered statistically significant. Results: The participants ranged from 18 to 47 years with the mean age of 27.8±6.9 years. The majority of the pregnant women were in the age groups 20-24 years and 25-29 years. The mean depression score for pregnant women was 7.87±5.2 and ranged from 0 to 23. The prevalence rate of depression symptoms was 31%. Maternal age was not significantly associated with depression and a significantly higher proportion of married pregnant women were depressed as compared to unmarried women at p=0.017. Pregnant women who smoke were significantly more likely to be depressed than those who do not smoke at p=0.002. Pregnant women without financial support from partnerwere significantly likely to be depressed than those who receive financial support at p-=0.002. A significantly greater proportion of pregnant women with partner violent were likely to be depressed than those with non-violent partner at p <0.001. Pregnant women in relationships with unemployed spouses were significantly likely to experience depression than the employed spouse at p=0.035. lastly, pregnant women in relationship with a spouse with lower educational level were significantly likely to be depressed than the other groups at p-.006. Conclusion: The prevalence of depression among pregnant women was high and the main risk factors involved in the onset of antenatal depression have highlighted a complex multifactorial aetiology. These are related to different sources of chronic diseases, psychosocial, environmental, obstetric and pregnancy- related risk factors have been highlighted. Correctly identifying women at risk of suffering from depression would provide an opportunity to target those women who would benefit from preventive and supportive interventions. Therefore, a psychosocial assessment, in the sense of a comprehensive and multidimensional evaluation of a woman's psychosocial circumstances should be common practice for all women during the antenatal period. Key concepts Antenatal care; Pregnancy; Childbearing; Depression; Psychosocial
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Antenatal care; Pregnancy; Childbearing; Depression; Psychosocial; Pregnancy; Child birth; Newborn -- Infants care; Midwifery; Depression, mental